2006
DOI: 10.1111/j.1365-2109.2006.01602.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of impact of aquaculture on Kolleru Lake (India) using remote sensing and Geographical Information System

Abstract: Aquaculture is one of the fastest growing food industries and the rapid growth of aquaculture worldwide has resulted in growing concerns about its impact on important ecosystems. Kolleru Lake, India's largest fresh water body, and Ramsar site have undergone tremendous changes due to the development of aquaculture. To assess the impact of aquaculture on Kolleru, satellite data were found appropriate because of the synoptic-detailed overview and accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 20 publications
0
12
1
Order By: Relevance
“…According to Jayanthi et al (2006), the overall lake loss occupied 11.38 km only area in lake bed 56.04 km whereas in the present study, a notable increase in the aquaculture encroachment in the lake bed was observed. The ecosystem of the lake was significantly affected due to agriculture and aquaculture, increased industrial activity, growing numbers of human settlers and infrastructure building such as roads, etc .…”
Section: Add-on Informationcontrasting
confidence: 56%
“…According to Jayanthi et al (2006), the overall lake loss occupied 11.38 km only area in lake bed 56.04 km whereas in the present study, a notable increase in the aquaculture encroachment in the lake bed was observed. The ecosystem of the lake was significantly affected due to agriculture and aquaculture, increased industrial activity, growing numbers of human settlers and infrastructure building such as roads, etc .…”
Section: Add-on Informationcontrasting
confidence: 56%
“…Hence, other anthropogenic activities, such as agriculture, urban expansion and tourism, contributed greatly to this reduction along the northern coast of the State of Pernambuco. In contrast to observed in the the largest fresh water body in India, Kolleru Lake, where 55.3% of the lake area was converted in rice field or aquaculture ponds (Jayanthi, Rekha, Kavitha & Ravichandran 2006).…”
Section: Discussionmentioning
confidence: 78%
“…It is cost-effective to control soil erosion, mainly for an agricultural dominant land-use class (Shen et al 2014;Sorando et al 2019). However, there is a requirement of knowledge to prevent soil erosion in Kolleru lake basin studies are imperative (Jayanthi et al 2006). At present, in the Kolleru Lake catchment, there is no gauge station to estimate soil loss; however, conventional methods are time consuming and cost-effective.…”
Section: Introductionmentioning
confidence: 99%